KONSEP PEMURIDAN YANG ALKITABIAH BERDASARKAN MATIUS 28: 19-20 BAGI PERTUMBUHAN IMAN JEMAAT - Daila Emilia Badeng; Nataliaday Karisma Gandhi; Agustina Pala’biran (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the biblical concept of discipleship based on Matthew 28:19–20 and its implications for the growth of the congregation's faith. Employing a qualitative method with a literature review approach, the study analyzes the Bible, theological texts, and relevant scholarly literature. The findings indicate that Matthew 28:19–20 establishes discipleship as the core of the Great Commission, encompassing the proclamation of the Gospel, baptism, teaching, and ongoing guidance. Discipleship is understood as a Christ-centered process of disciple-making facilitated through God's Word, exemplary living, and the work of the Holy Spirit that results in character transformation and spiritual maturity. Its implementation is realized through systematic biblical teaching, small groups, mentoring, and active involvement in church ministry. This concept fosters the growth of the congregation's faith, evidenced by spiritual maturity, Christian character, commitment to ministry, healthy fellowship, and the capacity to disciple others. Thus, biblical discipleship serves as a foundational element for the growth of the congregation's faith and the continuity of the church's mission in accordance with the Great Commission of Jesus Christ.